2019
DOI: 10.3847/1538-4357/ab0ec1
|View full text |Cite
|
Sign up to set email alerts
|

Gemini Imaging of the Host Galaxies of Changing-look Quasars

Abstract: Changing-look quasars are a newly-discovered class of luminous active galactic nuclei that undergo rapid ( 10 year) transitions between Type 1 and Type 1.9/2, with an associated change in their continuum emission. We characterize the host galaxies of four faded changing-look quasars using broadband optical imaging. We use gri images obtained with the Gemini Multi Object Spectrograph (GMOS) on Gemini North to characterize the surface brightness profiles of the quasar hosts and search for [O III] λ4959, λ5007 em… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 87 publications
4
39
0
Order By: Relevance
“…First, details of their host morphology should be searched for signatures of disrupted or ripples as may be caused by merged remnants. This is inspired by results reported by Charlton et al (2019), who clearly found such features in Gemini images of four CL-quasars. Second, CL-AGNs could be characterized by profile asymmetries in their broad emission lines.…”
Section: Conclusion and Discussionsupporting
confidence: 63%
“…First, details of their host morphology should be searched for signatures of disrupted or ripples as may be caused by merged remnants. This is inspired by results reported by Charlton et al (2019), who clearly found such features in Gemini images of four CL-quasars. Second, CL-AGNs could be characterized by profile asymmetries in their broad emission lines.…”
Section: Conclusion and Discussionsupporting
confidence: 63%
“…The red solid line is the boundary of the starforming main sequence. Charlton et al (2019) used the way of Sérsic indices versus colour diagram to separate galaxies as blue discs, green valley, and red spheroids, and found that all of their faded CL-AGN host galaxies are located in the green valley region. The possible reason is that we defined the star-forming main sequence in different ways.…”
Section: Global Star Formation Rate (Sfr) Bulge Kinematics and Axial Ratio (B/a)mentioning
confidence: 99%
“…The possible reason is that we defined the star-forming main sequence in different ways. We also used SFR versus stellar mass to check the faded CL-AGN host galaxies of Charlton et al (2019). Although there is only one target of Charlton et al (2019) that has been matched with the MPA-JHU catalogue, this galaxy is located in the star-forming main-sequence region.…”
Section: Global Star Formation Rate (Sfr) Bulge Kinematics and Axial Ratio (B/a)mentioning
confidence: 99%
See 1 more Smart Citation
“…Another big question on AGN physics is based on recently discovered changing look (CL) AGNs (e.g., LaMassa et al 2015;Sheng et al 2017;Stern et al 2018;Charlton et al 2019). This type of objects can exhibit transitions between AGN types by the emergence or disappearance of broad emission lines.…”
Section: Introductionmentioning
confidence: 99%